2012
DOI: 10.1016/j.metabol.2012.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of ApoB, ApoA1, and the ApoB/ApoA1 ratio in healthy schoolgirls, prospectively studied from mean ages 10 to 19 years: the Cincinnati National Growth and Health Study

Abstract: The objectives were to prospectively assess determinants of apolipoproteins B (ApoB), A1 (ApoA1), and the ApoB/ApoA1 ratio in 797 healthy black and white schoolgirls from mean ages 10 to 19. There was prospective 9-year follow-up, with measures of ApoB at mean ages 10, 12, 14,16 and 19, ApoA1at mean ages 12, 14, 16, and 19, and assessment of annual reports of delayed menstrual cyclicity (≥42 days) from ages 14 to 19. Studies of 402 black and 395 white healthy schoolgirls were done in public and private schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
2
6
0
Order By: Relevance
“…ApoB is the main protein in VLDL and LDL (atherogenic) particles, while ApoA1 is the main protein in HDL (anti-atherogenic) particles. This result is supported by an earlier 9-year follow-up study in school girls from childhood to adulthood, demonstrating that ApoB/ApoA1 ratio was associated with metabolic syndrome and it’s components 23 . In another prospective study, Juonala et al reported that ApoB and ApoA1 levels and their ratio in adolescence were associated with carotid artery intima-media thickness and brachial artery flow-mediated dilation in adulthood 24 .…”
Section: Discussionsupporting
confidence: 62%
“…ApoB is the main protein in VLDL and LDL (atherogenic) particles, while ApoA1 is the main protein in HDL (anti-atherogenic) particles. This result is supported by an earlier 9-year follow-up study in school girls from childhood to adulthood, demonstrating that ApoB/ApoA1 ratio was associated with metabolic syndrome and it’s components 23 . In another prospective study, Juonala et al reported that ApoB and ApoA1 levels and their ratio in adolescence were associated with carotid artery intima-media thickness and brachial artery flow-mediated dilation in adulthood 24 .…”
Section: Discussionsupporting
confidence: 62%
“…12 In addition, apolipoprotein B is known to be correlated with cardiometabolic risk factors in adolescents. 24 …”
Section: E534mentioning
confidence: 99%
“…We identified a cut-point value for ApoB:ApoA1 ratio of 0.45 that could have clinical utility in JSLE. However, ApoB:ApoA1 ratio is age dependent so further validation of age specific cut points is needed [ 37 , 52 , 53 ]. Differences in published ratios could be accounted for by different technologies used to assess ApoB and ApoA1 levels (mainly colorimetry-based compared to NMR used here) and the fasting status of the study participants (our study was performed on non-fasting patients).…”
Section: Discussionmentioning
confidence: 99%